Calling Allah with his names between theory and practice: Critical dogmatic study - Al-Sabateen, Rajeh Ibraheem (Dirasat: Shari’a and Law Sciences, 2021)
This paper discusses the issue of calling Allah with his most beautiful names and perfect attributes. This kind of calling "Du’aa" consists of two parts: The call of praise and worship and the call of asking for needs and demands. It also emphasizes that calling Allah with his most beautiful names and perfect attributes was implemented by Prophet Mohammad and the past prophets (p.b.u.t) during their lives. This research used the inductive method by extrapolating Sharia texts from the book and the Sunnah regarding supplication of Allah Almighty using his names and attributes. It also used the analytical method to differentiate between the supplication of Allah Almighty using his names and attributes on the one hand and the supplication of the attributes of Allah Almighty on the other hand by discussing the opinions and evidence of those who are against begging Allah Almighty using his attributes. In addition, it used the historical method by referring to selected models showing the supplication of the prophets using the names of Allah and his attributes, including the supplication of the prophets Ibrahim and Ishmael peace be upon them. Finally, the paper calls Muslims to make this kind of calling a method of life, and confirms the danger of its absence.